Cognitive functioning, financial literacy, and judgment in older age. (22nd August 2021) - Gerrans, Paul; Asher, Anthony; Earl, Joanne Kaa
Abstract: We investigate the relationships between financial literacy, financial judgment, and cognitive ability at older ages. We find people who actively manage their own retirement savings portfolios display greater levels of financial literacy and judgment than those who do not. We identify the different cognitive processes underlying financial judgment and decision‐making tasks versus those underlying learned concepts such as basic financial literacy. Although these decline at different rates the latter may potentially compensate for, and mask declines, in the former. We find an overall low propensity to seek financial advice which has no significant relationship with cognitive functioning. Our findings underscore the importance of monitoring cognitive ability in older ages.